2018
DOI: 10.1111/rda.13198
|View full text |Cite
|
Sign up to set email alerts
|

m‐carboxycinnamic acid bishydroxamide improves developmental competence, reduces apoptosis and alters epigenetic status and gene expression pattern in cloned buffalo (Bubalus bubalis) embryos

Abstract: Incomplete or aberrant reprogramming of nuclear genome is one of the major problems in somatic cell nuclear transfer. In this study, we studied the effect of histone deacetylase inhibitor m-carboxycinnamic acid bishydroxamide (CBHA) on in vitro development of buffalo embryos produced by Hand-made cloning. Cloned embryos were treated with CBHA (0, 5, 10, 20 or 50 μM) for 10 hr from the start of reconstruction till activation. At 10 μM, but not at other concentrations examined, CBHA increased (p < .05) the blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…We found that a majority of the epigenetic regulators, such as DNA methyltransferases (DNMTs), histone deacetylases (HDACs), and histone methyltransferases were upregulated in NT compared with IVF blastocysts which agrees with a previous report in bovine (Min et al, 2015). We have attempted correcting these critical nuclear reprogramming-related errors by treating NT embryos with epigenetic modifiers such as scriptaid (Panda et al, 2012), trichostatin A Selokar et al, 2016), valproic acid , and m-carboxycinnamic acid bishydroxymide (Agrawal et al, 2018a(Agrawal et al, , 2018b, which are HDAC inhibitors, to reduce histone acetylation, and 5-aza-2ʹ-deoxycytidine, a DNMT inhibitor, to reduce DNA methylation .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that a majority of the epigenetic regulators, such as DNA methyltransferases (DNMTs), histone deacetylases (HDACs), and histone methyltransferases were upregulated in NT compared with IVF blastocysts which agrees with a previous report in bovine (Min et al, 2015). We have attempted correcting these critical nuclear reprogramming-related errors by treating NT embryos with epigenetic modifiers such as scriptaid (Panda et al, 2012), trichostatin A Selokar et al, 2016), valproic acid , and m-carboxycinnamic acid bishydroxymide (Agrawal et al, 2018a(Agrawal et al, , 2018b, which are HDAC inhibitors, to reduce histone acetylation, and 5-aza-2ʹ-deoxycytidine, a DNMT inhibitor, to reduce DNA methylation .…”
Section: Discussionsupporting
confidence: 85%
“…We found that a majority of the epigenetic regulators, such as DNA methyltransferases (DNMTs), histone deacetylases (HDACs), and histone methyltransferases were upregulated in NT compared with IVF blastocysts which agrees with a previous report in bovine (Min et al, ). We have attempted correcting these critical nuclear reprogramming‐related errors by treating NT embryos with epigenetic modifiers such as scriptaid (Panda et al, ), trichostatin A (Saini et al, , ; Selokar et al, ), valproic acid (Selokar et al, ), and m‐carboxycinnamic acid bishydroxymide (Agrawal et al, , ), which are HDAC inhibitors, to reduce histone acetylation, and 5‐aza‐2′‐deoxycytidine, a DNMT inhibitor, to reduce DNA methylation (Saini et al, , ). Although treatments with these epigenetic modifiers resulted in significant improvements in blastocyst rate and embryo quality, as indicated by higher total cell number and lower level of apoptosis, whether these beneficial effects will be translated to improvements in live birth rate is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches have been used to correct the epigenetic reprogramming in cloned embryos such as treatment of somatic cells, oocytes and fused embryos with epigenetic modifiers or with oocytes or stem cells extract, overexpression or suppression of important regulatory genes in somatic cells or one cell stage cloned embryos ( Figure ). Buffalo somatic cells and/or fused embryos were treated with different epigenetic modulating agents, such as trichostatin A (TSA), 5-aza-2’-deoxycytidine (5-aza-dC), valproic acid (VPA) and m-carboxycinnamic acid bishydroxamide (CBHA) 14 16 17 18 . These studies showed that treatment of buffalo donor cells and/or one cell stage fused embryos or both with epigenetic modulators, alone or in combination, resulted in higher blastocyst production rates and lower level of apoptosis in generated cloned blastocysts 14 15 .…”
Section: Ways To Correct Epigenetic Reprogrammingmentioning
confidence: 99%
“…This study demonstrated that treatment of donor cells with VPA did not improve the blastocyst production rate. Agrawal et al 17 reported that 10 μM of CBHA could be used to improve the blastocyst rates and quality of cloned embryos.…”
Section: Use Of Epigenetic Modifiers In Buffalo Cloningmentioning
confidence: 99%
“…Until now genetic studies have mainly addressed genetic diversity (Barker et al ; Lei et al ; Kumar et al ; Zhang et al ; Colli et al ) and identification of genes and molecular markers that are associated with desirable traits (de Camargo et al ; Yusnizar et al ; Iannaccone et al ; Liu et al ), but to date only a few epigenetic studies have been carried out on water buffalo (Verma et al ; Agrawal et al ; Sharma et al ).…”
Section: Introductionmentioning
confidence: 99%